Solusi inovasi dan kemitraan peremajaan konstruksi kapal kayu nelayan 1 GT dan 3 GT berbasis teknologi material jenis kayu cepat tumbuh untuk mendorong industri galangan kapal masyarakat di wilayah pesisir Provinsi Riau - Imam Suprayogi; Fakhri Fakhri; Ronald Mangasi Hutauruk (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The main objective of community service is the application of the innovation of composite wood Material technology by utilizing wood species material with a fast growing species at Teluk Nilap Village, Kubu Babussalam District, Rokan Hilir Regency of Riau Province expected to provide solutions to the scarcity of wood materials with certain specifications for the rejuvenation of the community fishing vessel and the sustainability of the shipbuilding industry in the coastal region of Riau province. The method of approach used in this implementation is to combine the composite wood technology with the local wisdom culture of wood-based vessel material. The partnership of manufacturing full scale physical model timber vessel 1 GT and 3 GT fishermen in the community shipyard industry owned by H. Ali in Teluk Nilap village, Kubu Babussalam, Rokan Hilir District. The main result of devotion to society proved that the application of composite wood material technology using wood type fast growing for the construction of public fishing vessel size 1 GT and 3 GT (innovation) and has been applied to the Timber Shipyard Industry. The synergy of innovation and partnership encourages the improvement of the economy of fishermen communities in the coastal region of Riau province with the support of the independent shipyard industry.